Analysis Of The Use Of Online Registration (Whatsapp) On Outpatient Waiting Times At Kediri Regency Hospital - Herlinda Sri Puryani; Panca Radono; Agustin Widyowati (Universitas STRADA Indonesia, 2023)
Currently, the majority of Indonesians use whatsapp as a medium of communication. Referring to this fact, hospitals are now innovating by making it easier to speed up and reduce queues at the registration counter hammering online registration (whatsapp). The purpose of this study was to determine whether there is a relationship between the use of online registration (whatsapp) and the waiting time for outpatients. The research design used is descriptive quantitative. The total population is 100 people per day. The samples taken were 30 people. The sampling technique used is random sampling while the data collection tool used is questionnaire. The data analysis used is editing, coding, tabulating. Based on the results of the study, 18 respondents (60%) used online registration (whatsapp) quite well but as many as 24 respondents still waited for more than 60 minutes, namely (80%). The contingency coefficient calculation data produces a sig(p)= 0.906 with degree of meaningfulness of 0.05 (5%) the result is sig(p)>α then H0 which reads